GR_GERICHTE ZF 2008 56 vom 18. November 2008 , Bezirksgericht Prättigau/Davos - GR Gerichte (2008)
Forderung/Nichtbestehen einer Forderung | OR Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc. (OR 394-529)